2020
DOI: 10.15517/revedu.v45i1.41296
|View full text |Cite
|
Sign up to set email alerts
|

Competencias digitales en estudiantes de educación secundaria de una provincia del centro del Perú

Abstract: El estudio analiza el logro de competencias digitales de la población estudiantil de educación secundaria, según sexo y grado. La investigación es de enfoque cuantitativo, de diseño transversal descriptivo. La muestra estuvo compuesta por 665 estudiantes de las instituciones educativas públicas de una provincia de la región central del Perú. Se recogió información a través de un instrumento elaborado con base en la propuesta del Instituto Nacional de Tecnologías Educativas y de Formación del Profesorado (2017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
2
0
3
Order By: Relevance
“…Students' level of digital competence in this area qualifies as a pass (or foundation level) in knowledge and skill. These results are consistent with the findings of other studies that also assessed this competence area in Spanish basic-education students [14,16], but disagree with studies that claim that Peruvian secondary-education students achieved adequate results in the addressed digital competences (interacting through technologies, sharing information and content, collaborating through digital channels, netiquette, and managing digital identity) [17]. In the attitude dimension, assessments proved to be very positive, which is in line with the results of other studies [73][74][75].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Students' level of digital competence in this area qualifies as a pass (or foundation level) in knowledge and skill. These results are consistent with the findings of other studies that also assessed this competence area in Spanish basic-education students [14,16], but disagree with studies that claim that Peruvian secondary-education students achieved adequate results in the addressed digital competences (interacting through technologies, sharing information and content, collaborating through digital channels, netiquette, and managing digital identity) [17]. In the attitude dimension, assessments proved to be very positive, which is in line with the results of other studies [73][74][75].…”
Section: Discussionsupporting
confidence: 81%
“…The digital competences that it covers are: interacting through technologies, sharing information and content, engaging in online citizenship, collaborating through digital channels, netiquette, and managing digital identity. In recent years, research focused on this competence area following the European Digital Competence Framework [14][15][16][17].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The COVID-19 pandemic transformed the homes of students into places of study, revealing the shortcomings in terms of resources to face this challenge. Under these circumstances, not all students achieved the expected level of studies due to the limited mastery of digital competences (Orosco, Gómez, Pomasunco, Salgado & Álvarez, 2021). In the research conducted here, it was observed that the meager socioeconomic income, limited access to electricity and the inadequate technological infrastructure of the educational institutions affected the levels of MIL achievement; it was the La Joya UGEL (in a rural non-urban area) where the least development was seen.…”
Section: Discussionmentioning
confidence: 66%
“…En esa línea, se realizaron estudios (Fernández-Planells y Figueras, 2012;García-Ruiz et al, 2020;Mateus et al, 2019;Santibáñez et al, 2016) cuyos hallazgos indican diversos niveles de desarrollo de la competencia en sus diferentes dimensiones. No obstante, en la literatura reciente, existen estudios Barredo et al, 2021;Orosco et al, 2020; que se enfocan solo en una de ellas. Análogamente, este estudio aborda la competencia desde una dimensión: ideología y valores.…”
Section: Conceptualizando La Competencia Mediáticaunclassified
“…Este estudio pretende comprender cómo analiza la audiencia peruana las películas violentas nacionales, específicamente desde la dimensión de ideología y valores de su competencia mediática (Ferrés y Piscitelli, 2012). A diferencia de la mayoría de estudios, que abordan este fenómeno cuantitativamente (Gonzáles, Turpo y Suárez, 2020;Marín-Gutiérrez et al, 2020;Orosco et al, 2020;Barredo et al, 2021), se propone una mirada cualitativa, que transciende la autopercepción y demuestra la capacidad crítica de la audiencia (Mateus et al, 2019).…”
Section: Introductionunclassified